2012
DOI: 10.1177/1938640012439604
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Multimedia as an Adjunct to the Informed Consent Process for Ankle Ligament Reconstruction Surgery

Abstract: Therapeutic Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The use of multimedia aids (computer-based, patient-controlled interactive educational tool) has been reported to have a significant effect on knowledge transfer and patient learning 38. These aids are an adjunct to physician–patient encounters and not a substitute for them 75. The use of multimedia programmes developed specifically for preadmission use provides patients with opportunities to access detailed, high-quality information regarding their upcoming surgery, combined with pertinent details of their hospitalisation and treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multimedia aids (computer-based, patient-controlled interactive educational tool) has been reported to have a significant effect on knowledge transfer and patient learning 38. These aids are an adjunct to physician–patient encounters and not a substitute for them 75. The use of multimedia programmes developed specifically for preadmission use provides patients with opportunities to access detailed, high-quality information regarding their upcoming surgery, combined with pertinent details of their hospitalisation and treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…The improved post‐module scores likely stem from the multimedia module utilizing a variety of learning modalities including graphical representations, verbal descriptions and written explanations. Such a model has been shown to effectively address a number of different learning styles …”
Section: Discussionmentioning
confidence: 99%
“…The use of multimedia aids to assist in patient education and improve the informed consent process has been shown to be a feasible option in orthopaedic populations considering elective surgical management for the treatment of pain . The bunion population presents a unique group of orthopaedic patients, as the majority are women who are concerned about pain as well as cosmetic appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that CAI can increase patients' knowledge about health topics and assist in patient satisfaction during the informed consent process for surgery. 7,8 Recent randomized trials have even suggested that patients are able to retain more information from a computer based education system alone than from static illustrative diagram-based instruction provided by their physician. 9 However, there is a paucity of published studies examining patient counseling using computer based education programs for urogynecologic conditions.…”
Section: Introductionmentioning
confidence: 99%